The complete chloroplast genome of Ostrya rehderiana. (1st November 2016) - Li, Yuanshuo; Bi, Hao; Liu, Bingbing; Guo, Xinyi; Hao, Guoqian; He, Qi; Ma, Tao
Abstract: The complete chloroplast sequence of Ostrya rehderiana is 159 347 bp in length, containing 85 protein-coding genes, 8 ribosomal RNA genes, and 31 transfer RNA genes. The circular genome exhibits a typical chloroplast genome structure comprising a large single copy region of 88 552 bp, a small single copy region of 18 941 bp and a pair of inverted repeats of 25 927 bp. The overall GC content of the chloroplast genome is 36.5%. Phylogenetic analysis of O. rehderiana sequence together with 12 complete chloroplast genomes revealed a basal placement of O. rehderiana within the Fagales species.